Rj4, a Gene Controlling Nodulation Specificity in Soybeans, Encodes a Thaumatin-Like Protein But Not the One Previously Reported. Issue 1 (18th November 2015) - Tang, Fang; Yang, Shengming; Liu, Jinge; Zhu, Hongyan
Abstract : A thaumatin-like protein regulates gene-for-gene interaction with specific rhizobial strains and controls nodulation specificity in soybeans. Abstract: Rj4 is a dominant gene in soybeans ( Glycine max ) that restricts nodulation by many strains of Bradyrhizobium elkanii . The soybean- B. elkanii symbiosis has a low nitrogen-fixation efficiency, but B. elkanii strains are highly competitive for nodulation; thus, cultivars harboring an Rj4 allele are considered favorable. Cloning the Rj4 gene is the first step in understanding the molecular basis of Rj4 -mediated nodulation restriction and facilitates the development of molecular tools for genetic improvement of nitrogen fixation in soybeans. We finely mapped the Rj4 locus within a small genomic region on soybean chromosome 1, and validated one of the candidate genes as Rj4 using both complementation tests and CRISPR/Cas9-based gene knockout experiments. We demonstrated that Rj4 encodes a thaumatin-like protein, for which a corresponding allele is not present in the surveyed rj4 genotypes, including the reference genome Williams 82. Our conclusion disagrees with the previous report that Rj4 is the Glyma.01G165800 gene (previously annotated as Glyma01g37060). Instead, we provide convincing evidence that Rj4 is Glyma.01g165800-D, a duplicated and unique version of Glyma.01g165800, that has evolved the ability to control symbiotic specificity.